2020
DOI: 10.26656/fr.2017.4(5).155
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on proximate and antinutritional factors of dehulled and undehulled fermented Lyon bean (Mucuna cochinchinensis)

Abstract: The impact of fermentation times and temperatures on the proximate composition and anti -nutrient content of dehulled and un-dehulled Mucuna cochinchinensis flour were investigated. Dehulled and un-dehulled Lyon beans were subjected to fermentation at 30° C and 45°C for 24, 48 and 72 hrs respectively and the fermented seeds were processed into flour. Results obtained revealed that the fermentation time/day had an effect on the proximate composition of the beans causing an appreciable increase in the crude prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…A 3% decrease in the carbohydrate content reported during the fermentation of red bean (Phaseolus angularis) was attributed to the use of carbohydrate as the energy source for fungal growth [148]. Different authors [130,144,146,149,153,178,190,191] have all equally reported reductions in carbohydrate levels during the fermentation of African oil bean (7%), tempeh (0.7%), cowpea (3%), mahogany bean (up to 61%), kidney bean (17%), lentil (6%), African yam bean (4%) and Lyon bean (up to 26%), and ascribing such reductions to the use of carbohydrate-related compounds as the energy source by fermenting microorganisms for growth and metabolism as well as the conversion of oligosaccharides to simple sugars. The observed varying decreases in the carbohydrate values of these legumes could be due to differences in the inherent composition (e.g., amylose, amylopectin and the structural composition of carbohydrates), plant varieties, species as well as fermenting microorganisms present during the fermentation process.…”
Section: Carbohydrate Energy and Starch Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 3% decrease in the carbohydrate content reported during the fermentation of red bean (Phaseolus angularis) was attributed to the use of carbohydrate as the energy source for fungal growth [148]. Different authors [130,144,146,149,153,178,190,191] have all equally reported reductions in carbohydrate levels during the fermentation of African oil bean (7%), tempeh (0.7%), cowpea (3%), mahogany bean (up to 61%), kidney bean (17%), lentil (6%), African yam bean (4%) and Lyon bean (up to 26%), and ascribing such reductions to the use of carbohydrate-related compounds as the energy source by fermenting microorganisms for growth and metabolism as well as the conversion of oligosaccharides to simple sugars. The observed varying decreases in the carbohydrate values of these legumes could be due to differences in the inherent composition (e.g., amylose, amylopectin and the structural composition of carbohydrates), plant varieties, species as well as fermenting microorganisms present during the fermentation process.…”
Section: Carbohydrate Energy and Starch Fractionsmentioning
confidence: 99%
“…A 29% decrease in phytic acid in fermented soymilk was ascribed to the action of phytase and β-glucosidase produced by fermenting microbes [197]. Olaleye et al [190] reported an increased nutritional content as well as a significant reduction in oxalate (16.5-68%), phytate (13.7-26%) and tannin (9.2-25.7%), following the fermentation of beans for 72 h at 45 • C with no reported mechanism. As described in various studies, the fermentation of cereals and legumes reduces tannins via hydrolysis by tannase, which catalyses the hydrolysis of ester and depside bonds, yielding gallic acid and glucose [168,207,208].…”
Section: Antinutritional Factorsmentioning
confidence: 99%
“…The phytic acid content in legumes, cereals, oilseeds, pollens, and nuts is 1% to 5%, which is comparable to barnyard millet 44 . Phytic acid is considered an antinutritional compound, as, like other antinutrients, it binds with minerals and hinders their bioavailability of multivalent cations, such as Ca 2+ , Mg 2+ , Zn 2+ , Fe 2+ , and Fe 3+ , by establishing insoluble metal complexes and rendering them unavailable to humans and animals 45 . It also inhibits various digestive enzymes such as pepsin, α‐amylase, and trypsin.…”
Section: Resultsmentioning
confidence: 99%
“…44 Phytic acid is considered an antinutritional compound, as, like other antinutrients, it binds with minerals and hinders their bioavailability of multivalent cations, such as Ca 2+ , Mg 2+ , Zn 2+ , Fe 2+ , and Fe 3+ , by establishing insoluble metal complexes and rendering them unavailable to humans and animals. 45 It also inhibits various digestive enzymes such as pepsin, α-amylase, and trypsin. The phytate: Iron ratio (Phy: Fe) was found to be greater than 1 in all the samples (Table 2), which means iron is in an available form and is not affected by the presence of phytic acid.…”
Section: Antinutritional Factorsmentioning
confidence: 99%
“…Phytates lower mineral bioavailability by chelating minerals to form complex salts (Akande et al, 2010; Samtiya et al, 2020). Its presence in food impairs the utilization of phosphorous, iron, calcium, magnesium, manganese, copper, and zinc (Agarwal, 2016; Fernandes et al, 2010; Gemede & Ratta, 2014; Olaleye et al, 2020). Tannins precipitate proteins through hydrogen bonding and hydrophobic interactions, decreasing their digestibility (Akande et al, 2010; Fernandes et al, 2010; Ferreira et al, 2019).…”
Section: Introductionmentioning
confidence: 99%